2019
DOI: 10.1108/ijoem-07-2018-0404
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of precious metals and adaptive market hypothesis

Abstract: Purpose The purpose of this paper is to boost the existing literature on adaptive market hypothesis (AMH) as it first time links predictability of gold, silver and metal returns with AMH which permits the predictability of returns to vary over time. Design/methodology/approach To know whether commodity (gold, silver and metal) market is efficient or not, the commodity returns are observed by using appropriate linear time series tests (variance ratio test, runs test and auto-correlation test). To capture the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…AMH have been verified in Equity markets [3][4][5][6] Forex markets [2,7], Commodity markets [8,9] and cryptocurrency markets [10,11]. Here, our purpose is to test the validity of AMH in the fine wine market.…”
Section: Introductionmentioning
confidence: 98%
“…AMH have been verified in Equity markets [3][4][5][6] Forex markets [2,7], Commodity markets [8,9] and cryptocurrency markets [10,11]. Here, our purpose is to test the validity of AMH in the fine wine market.…”
Section: Introductionmentioning
confidence: 98%
“…Using a time-varying approach to examine bond market efficiency in the U.S., the U.K., South Africa, and India, Charfeddine et al (2018) found evidence in favor of the AMH in characterizing the behavior of government bond returns. Likewise, Shahid et al (2019a) hold a similar view for the behavior of commodity markets after they examine commodity (gold, silver, and metal) market efficiency from 1992 to 2016 via linear time series models (variance ratio test, runs test, and autocorrelation test). Charles et al (2012) evaluate time-varying return predictability of major foreign exchange rates over the period from 1974 to 2009 by applying the wild bootstrap automatic variance ratio test, generalized spectral test, and Dominguez-Lobato consistent tests.…”
Section: A Literature Reviewmentioning
confidence: 93%
“…Numerous previous studies have focused on market efficiency testing several versions of the EMH. Some focus on market efficiency in the energy markets (Khediri & Charfeddine, 2015;Ghazani & Ebrahimi, 2019), bond markets (Charfeddine et al, 2018), stock markets (Alvarez-Ramirez et al, 2012;Urquhart & Hudson, 2013;Hiremath & Kumari, 2014;Rodriguez et al, 2014;Xiong et al, 2019), commodities markets (Shahid et al, 2019a), cryptocurrencies (Khursheed et al, 2020) and foreign exchange markets (Charles et al, 2012) within the framework of AMH.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Kumar (2014), Maciel (2018), and Pernagallo and Torrisi (2019) found evidence of long-range dependence in most Indian sectoral indices, the Brazilian stock market, and emerging economies respectively. Beyond that, Shahid et al (2020) concluded that past prices of metals would be helpful to predict future prices in the New York Stock Exchange, implying the possible long memory in future markets.…”
Section: Literature Reviewmentioning
confidence: 99%